Structure and functionality of polyelectrolyte brushes : a surface force perspective - Xu, Xin (2020)
The unique functionality of polyelectrolyte brushes depends on several types of specific interactions, including solvent structure effects, hydrophobic forces, electrostatic interactions, and specific ion interactions. Subtle variations in the solution environment can lead to conformational and surface structural changes of the polyelectrolyte brushes, which are mainly discussed from a surface-interaction perspective in this Focus Review. A brief overview is given of recent theoretical and experimental progress in the structure of polyelectrolyte brushes in various environments. Two important techniques for surface-force measurements are described, the surface forces apparatus (SFA) and atomic force microscopy (AFM), and some recent results on polyelectrolyte brushes are shown. Lastly, this Focus Review highlights the use of these surface-grafted polyelectrolyte brushes in the creation of functional surfaces for various applications, including nonfouling surfaces, boundary lubricants, and stimuli-responsive surfaces.